Collectie Thompson uit Pittsburgh. - Haags Gemeentemuseum, Den Haag (Den Haag : Gemeentemuseum Den Haag, 1961)
Arp, Jean ; Albers, Josef ; Bazaine, Jean ; Bluhm, Norman ; Boardman, Seymour ; Bonnard, Pierre ; Borduas, Paul-Emil ; Braque, Georges ; Cézanne, Paul ; Consagra, Pietro ; Degas, Edgard ; Delaunay, Robert ; Derain, André ; Dubuffet, Jean ; Dufy, Raoul ; Ensor, James ; Fautrier, Jean ; Giacometti, Alberto ; van Gogh, Vincent ; Goldberg, Michael ; Gorky, Arshile ; Gris, Juan ; etc.
Collectie Thompson uit Pittsburgh, Gemeentemuseum Den Haag, 17 februari - 9 april 1961
boek